Strategi Dalam Meningkatkan Survival Rate Pada Penderita Henti Jantung Di Luar Rumah Sakit Out- Hospital Cardiac Arrest - Hendri Purwadi; M. Hendra Fatriadi (Jurnal Pengabdian Bidang Kesehatan, 2023)
The incidence of out-hospital cardiac arrest (OHCA) continues to increase. The survival rates of out hospital cardiac arrest decrease by 7-10% every minute. Therefore, Emergency medical services (EMS) as a part of the chain of survival needs to implement paramount strategies in order to increase survival rates. Socialization and discussion to strengthen the strategy has been conducted on December 2023 which involved pre-hospital team of Manambai Abdulkadir hospital (8 nurses, 1 doctor). It was followed by developing action plans. The pre-hospital team has chosen 2 of 10 action plans (rapid dispatch and community CPR) as main strategy to improve survival rates of out-hospital cardiac arrest patients. The Manambai Hospital are recommended to improve their support to develop human resources, medical equipment and funding to EMS team in order to improving survival rates of OHCA patients